2004
DOI: 10.1111/j.1601-5223.2000.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics of two Species of Paratelmatobius (Anura: Leptodactylidae), with Phylogenetic Comments

Abstract: In this paper we provide a cytogenetic analysis of Paratelmatobius cardosoi and Paratelmatobius poecilogaster. The karyotypes of both species showed a diploid number of 24 chromosomes and shared some similarity in the morphology of some pairs. On the other hand, pairs 4 and 6 widely differed between these complements. These karyotypes also differed in their NOR number and location. Size heteromorphism was seen in all NOR-bearing chromosomes of the two karyotypes. In addition, both karyotypes showed small centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
9

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 24 publications
0
18
1
9
Order By: Relevance
“…However, an explanation for differences among species in their susceptibility to molecular reorganization of rDNA clusters is still lacking. Results of the present study contrast with the major pattern of only one chromosome pair with NOR that is found in the other Phyllomedusa and related species studied so far; however, multiple NORs have been described in several other anuran species (e.g., Wiley et al, 1989;Lourenço et al, 1998Lourenço et al, , 2000Veiga-Menoncello et al, 2003;Amaro-Ghilardi et al, 2006;Silva et al, 1999, indicating that this variation is common in this group.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…However, an explanation for differences among species in their susceptibility to molecular reorganization of rDNA clusters is still lacking. Results of the present study contrast with the major pattern of only one chromosome pair with NOR that is found in the other Phyllomedusa and related species studied so far; however, multiple NORs have been described in several other anuran species (e.g., Wiley et al, 1989;Lourenço et al, 1998Lourenço et al, , 2000Veiga-Menoncello et al, 2003;Amaro-Ghilardi et al, 2006;Silva et al, 1999, indicating that this variation is common in this group.…”
Section: Discussioncontrasting
confidence: 54%
“…Similar NOR-length heteromorphisms were found in other anurans (Schmid, 1982;Lourenço et al, 2000;Busin et al, 2000;Bruschi et al, 2012), and this variation has been formerly attributed to tandem amplification of rRNA genes or of a whole NOR segment (Schmid, 1982;King et al, 1990). Schmid (1982) suggested that amplified NORs would be lethal in their homomorphic state, since the chromosome rearrangement could cause additional structural alterations in the NOR-adjacent segments that contain some functionally important genes.…”
Section: Discussionmentioning
confidence: 77%
“…The karyotype of Lithodytes lineatus, another taxon included in Leptodactylus by Frost et al (2006), are composed of 18 biarmed chromosomes (Bogart 1970) and Vanzolinius discodactylus has a 2n=22 karyotype very similar to the other Leptodactylus above referred (Heyer and Diment 1974). Results of Frost et al (2006) and Grant et al (2006) suggest that the clade including Paratelmatobius and Scythrophrys is the sister group of Leptodactylus, and in both genus karyotypes with 24 chromosomes were observed (De Lucca et al 1974, Lourenço et al 2000, 2001, 2003. Taking a conservative approach to the contents of Leptodactylus (i.e., excluding Adenomera, Lithodytes, and Vanzolinius) the distinct diploid number of L. silvanimbus could be interpreted according to two different hypotheses.…”
Section: Discussionmentioning
confidence: 93%
“…It is also interesting to note that there was no intraindividual variability in P. poecilogaster, despite the two NOR-bearing chromosome pairs in this karyotype (chromosome pairs 8 and 10; Lourenço et al, 2000). Moreover, all the species studied, as well as the individuals from the two group I Scythrophrys populations, could be distinguished from each other by the size of the digested fragments.…”
Section: Discussionmentioning
confidence: 84%
“…The available information about Paratelmatobius and Scythrophrys includes cytogenetic analyses showing interspecific variation in the NOR location in three karyotypes of Paratelmatobius (Lourenço et al, 2000;Lourenço et al, 2003) and two of Scythrophrys (Lourenço et al, in press). However, the organization of the rDNA genes in these genera is not known yet.…”
Section: Introductionmentioning
confidence: 99%